Spread of the blaOXA-23-containing Tn2008 in carbapenem-resistant Acinetobacter baumannii isolates grouped in CC92 from China - Chen, Yisheng; Gao, Jing; Zhang, Haomin; Ying, Chunmei (Frontiers in Microbiology, 2017)
The rapid expansion of carbapenem-resistant Acinetobacter baumannii (CRAB) clinical isolates is a big issue. We investigated the antibiotic susceptibility, molecular epidemiology and resistance gene of A. baumannii collected at two hospitals in Shanghai, China. Besides, the A. baumannii PCR-based replicon typing method (AB-PBRT) was conducted to categorize the plasmids into homogeneous groups on the basis of replicase genes. Most CRAB isolates showed high-level resistance to almost all antibiotics but retain susceptibility to colistin and tigecycline. A total of 101 isolates carried blaOXA-51-like gene. Sequencing identified the presence of blaOXA-66 for CRAB isolates. blaOXA-23 gene were discovered in all CRAB isolates. Each CRAB isolate contained 1 to 3 of 19 different plasmid replicase (rep) gene homology groups (GRs) and the GR6 (repAci6) was ubiquitous. Genotyping by Multilocus Sequence Typing (MLST) showed 7 defined MLST patterns and 3 novel STs were found. eBURST analysis indicated they were all grouped in CC92 (GCII) with the most frequent ST208 (50%). Two blaOXA-23-bearing transposons were found: Tn2006 and Tn2008. Tn2008 were detected in 54 (96.4%) isolates and Tn2006 in 2 remaining isolates. The blaOXA-23 carbapenem gene was vitally associated with repAci6 plasmid belong to CC92 clonal group. Our survey revealed severe drug resistance in A. baumannii isolates. Tn2008-containing CC92 A. baumannii were endemic, which may facilitate the blaoxa23 dissemination.